2012
DOI: 10.1164/rccm.201111-2023oc
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid–related Orphan Receptor-α Is Induced in the Setting of DNA Damage and Promotes Pulmonary Emphysema

Abstract: Rationale: The discovery that retinoic acid-related orphan receptor (Rora)-a is highly expressed in lungs of patients with COPD led us to hypothesize that Rora may contribute to the pathogenesis of emphysema. Objectives: To determine the role of Rora in smoke-induced emphysema. Methods: Cigarette smoke extract in vitro and elastase or cigarette smoke exposure in vivo were used to model smoke-related cell stress and airspace enlargement. Lung tissue from patients undergoing lung transplantation was examined for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…The inhibition of the pro-inflammatory transcription factor nuclear factor-kB RORA could be regulated by RORA as well [40]. In addition, RORA involve with the response to DNA damage, and loss of RORA protect against airspace enlargement in animal models of emphysema [41]. Moreover, variants of RORA were reported to be associated with the risk of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of the pro-inflammatory transcription factor nuclear factor-kB RORA could be regulated by RORA as well [40]. In addition, RORA involve with the response to DNA damage, and loss of RORA protect against airspace enlargement in animal models of emphysema [41]. Moreover, variants of RORA were reported to be associated with the risk of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…RORA binds to the promoter region of let-7α2 gene in lung cancer A549 cells [40]. Shi et al said that silencing of RORA attenuated the cell apoptosis while overexpression of RORA enhanced the cell apoptosis in patients with pulmonary emphysema [41]. Also, role of RORA associated with T cell cytokines in the non-small cell lung cancer was also performed by Neurath [42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the molecular clock regulates cellular proliferation and senescence as well as DNA damage/repair (35)(36)(37). Thus, future studies are needed to determine the changes of clock molecules in different lung compartments (inflammatory versus structural cells) and their cell-specific roles in inflammatory responses and cellular senescence/ proliferation in patients with COPD.…”
Section: Original Researchmentioning
confidence: 99%